PEMBUATAN SEDIAAN PAREM DARI DAUN MENGKUDU (MORINDA CITRIFOLIA) DENGAN CAMPURAN BERAS, KENCUR, JAHE UNTUK LUKA BAKAR - Latifa, Ayi Noer Afni; Putra, Risa Kota; Farhan, Farhan (Sekolah Tinggi Ilmu Kesehatan Holistik, 2017)
Background: Plants that play an important role in healing this burn is mengkudu (Morinda Citrifolia), which is used for parem ingredients of the leaves. The other ingredients used to make preparations parem of rice, ginger and Kaempferia galanga. Rice is a usefulness for heat dissipation in the burned wound, ginger properties to reduce inflammation in the skin, and kaempferia galanga to remove burns. The aim: The aim of this research is to describe the process of processing into preparations parem of noni leaf with a mixture of rice flour, kaempferia galanga, and Ginger. Methode: The methodology used in this research is descriptive qualitative, by taking some collection of journals from previous studies and from observations by interviews with ten people of Sawah Kulon Village. Preparation use noni leaves as a main ingredient as much as 250g with material mixtures using rice flour 500g, kaempferia galanga 10g, ginger 10g and a glass of water (at about 250ml). The process of making parem in this research is by mixing all the ingredients in a container to form a dough, then the dough is formed into flat circles with each weighing between 4-7g. Result: This research was conducted organoleptic tests for three weeks with the results showed that no significant changes occurred, from the shape, color, odor and mold growth. Conclusion: Parem resulting from noni leaves and rice flour mixture, kaempferia and ginger can last for three weeks.